Behavioral Interventions in Schools: Evidence-Based Positive Strategies (2nd Ed.). 2019
DOI: 10.1037/0000126-014
|View full text |Cite
|
Sign up to set email alerts
|

Classroom pivotal response teaching.

Abstract: Providing educational services to children with autism spectrum disorder (ASD) poses a challenge to educators. Although an increasing number of evidence-based practices (EBPs) have been developed for this population (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Recently, several studies have investigated the adaptation of PRT to the classroom context and reported that teachers are able to implement PRT techniques, resulting in positive outcomes on the child’s target goals [e.g. 28 , 29 ]. Nevertheless, research to date has focused on only one setting (i.e.…”
mentioning
confidence: 99%
“…Recently, several studies have investigated the adaptation of PRT to the classroom context and reported that teachers are able to implement PRT techniques, resulting in positive outcomes on the child’s target goals [e.g. 28 , 29 ]. Nevertheless, research to date has focused on only one setting (i.e.…”
mentioning
confidence: 99%